2016
DOI: 10.1063/1.4960836
|View full text |Cite
|
Sign up to set email alerts
|

Silicon based solar cells using a multilayer oxide as emitter

Abstract: In this work, n-type silicon based solar cells with WO3/Ag/WO3 multilayer films as emitter (WAW/n-Si solar cells) were presented via simple physical vapor deposition (PVD). Microstructure and composition of WAW/n-Si solar cells were studied by TEM and XPS, respectively. Furthermore, the dependence of the solar cells performances on each WO3 layer thickness was investigated. The results indicated that the bottom WO3 layer mainly induced band bending and facilitated charge-carriers separation, while the top WO3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Gerling [38] and Wu [39] compared the effects of the V 2 O x , MoO x , and WO x hole-selective contacts on the SHJ solar cells, reaching a conclusion that V 2 O x is a better candidate for the hole-selective contact. Shen and co-workers proposed a multi-layered emitter (i.e., hole-selective contact) based on a TMO/Ag/TMO structure [33,81]. The first TMO layer to make contact with c-Si caused band bending on the c-Si surface, achieving carrier selectivity.…”
Section: Tmo Hole-selective Contactsmentioning
confidence: 99%
“…Gerling [38] and Wu [39] compared the effects of the V 2 O x , MoO x , and WO x hole-selective contacts on the SHJ solar cells, reaching a conclusion that V 2 O x is a better candidate for the hole-selective contact. Shen and co-workers proposed a multi-layered emitter (i.e., hole-selective contact) based on a TMO/Ag/TMO structure [33,81]. The first TMO layer to make contact with c-Si caused band bending on the c-Si surface, achieving carrier selectivity.…”
Section: Tmo Hole-selective Contactsmentioning
confidence: 99%
“…Meanwhile, some researchers focus on the passivating contact by employing the TMO/metal/TMO multilayer structure as an emitter, [177][178][179] which shows high conductivity and high transmittance for the front contact. 180 For example, Wu et al investigated the effect of the intermediate metal layer on the V 2 O x /metal/V 2 O x structure and found that the intermediate metal with a high W F and a thinner thickness will decrease ρ c. 181 The c-Si solar cell employing the optimized V 2 O x /4-nm Au/V 2 O x as the emitter achieves an efficiency of 19.02%, which is 1.44% higher than that of the c-Si solar cell using a single layer of V 2 O x as the emitter. Yet the poor longterm stability of the structure still needs to be resolved, and the efficiency drops by nearly 50% over 100 days.…”
Section: Novel Structure Designmentioning
confidence: 99%
“…DMD multilayers that are deposited at room temperature and thus do not induce thermal damage to the mechanical, electrical, and optical properties of underlying layers can be optimized by changing the material types, layer thicknesses, and refractive indices without the need of post deposition texturing. Therfore, DMDs are considered as promising candidates to replace standard TCEs in solar cells . The electrical properties of DMD structures can be tuned by varying the layer thicknesses and material choice.…”
Section: Introductionmentioning
confidence: 99%
“…Therfore, DMDs are considered as promising candidates to replace standard TCEs in solar cells. [16][17][18][19] The electrical properties of DMD structures can be tuned by varying the layer thicknesses and material choice. Thus, these DMD TCEs can be fabricated with materials that come at lower cost than conventional TCEs and can be prepared by conventional deposition techniques, while achieving superior optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%